Bridging the Gap between Language and Literature: Teaching English in Bangladesh at Tertiary Level - Masrufa Ayesha Nusrat (Universitas Negeri Makassar, 2015)
Using literary material for developing language skills has gained new attention for both L1 and L2 learners in the last two decades. In my paper I would like to explore the possibilities and loopholes of teaching language through literature in Bangladesh at the tertiary level. Our language classes follow traditional lecture-based teaching techniques and use almost no literary materials for teaching language. Mostly ‘referential’ materials are taught by Communicative Language Teaching (CLT) method which are exclusively confined to everyday real-life situational use and does not engage learners’ imaginative faculties. Therefore, I have tried to demonstrate how literary texts or ‘representational texts’ can develop English proficiency, foster critical thinking and encourage creative language use. I have also critiqued our material selection; teaching approaches; evaluation; and rote learning during exam. As a result a gap has long been created between language and literature at the tertiary level, hampering language acquisition. Although critical practices like, Literary Theory and Cultural Studies, have enriched our academia and generated impressive curriculum (such as World Literature in English, Comparative Literature and Applied Linguistics and ELT), learners’ basic linguistic competence has declined considerably. I have tried to recommend ways to solve these problems by introducing language-based teaching approach and integrating language with literature. Keywords: representational material, referential material, language-based approach, stylistics, literature with a small ‘l’, literary language, imaginative language use, literary and linguistic competence, product-based and process-based teaching and learning